Bone turnover markers in medicamentous and physiological hyperprolactinemia in female rats - Radojković, Danijela; Pešić, Milica; Ristić, Tatjana (Vojnosanitetski pregled, 2014)
Background/Aim. There is a lack of data on the effects of prolactin on calcium metabolism and bone turnover in hyperprolactinemia of various origins. The aim of this study was to compare the influence of medicamentous and physiological hyperprolactinemia on bone turnover in female rats. Methods. Experimental animals (18 weeks old, Wistar female rats) were divided as follows: the group P – 9 rats, 3 weeks pregnant; the group M3–10 rats that were intramuscularly administrated sulpirid (10 mg/kg) twice daily for 3 weeks, the group M6 – 10 rats that were intramuscularly administrated with sulpirid (10 mg/kg) twice daily for 6 weeks, and age matched nulliparous rats as the control group: 10 rats, 18-week-old (C1) and 7 rats, 24 weeks old (C2). Laboratory investigations included serum ionized calcium and phosphorus, urinary calcium and phosphorous excretion, osteocalcin and serum procollagen type 1 N-terminal propeptide (P1NP). Results. Experimental animals in the group P compared to the control group, displayed lower mean serum ionized calcium (0.5 ± 0.2 vs 1.12 ± 0.04 mmol/L; p < 0.001); higher mean serum phosphorus (2.42 ± 0.46 vs 2.05 ± 0.2 mmol/L; p < 0.05); increased urinary calcium (3.90 ± 0.46 vs 3.05 ± 0.58; p < 0.01) and significantly increased P1NP (489,22 ± 46,77 vs 361.9 ± 53,01 pg/mL; p < 0.001). Experimental animals in the group M3 had significantly decreased P1NP, compared to the contol group. Prolongated medicamentous hyperprolactinemia (the group M6) induced increased serum ionized calcium (1.21 ± 0.03 vs 1.15 ± 0.02 mmol/L; p < 0.001); decreased serum phosphorus (1.70 ± 0.13 vs 1.89 ± 0.32 mmol/L; p < 0.001); decreased osteocalcin and P1NP. Conclusions. Physiological hyperprolactinemia does not have such harmful effect on bone metabolism as medicamentous hyperprolactinemia. Chronic medicamentous hyperprolactinemia produces lower serum levels of bone formation markers. Assessment of bone turnover markers in prolongated medicamentous hyperprolactinemia provides an opportunity for earlier diagnosis of bone metabolism disturbances and should be considered as mandatory.